Diffuse pulmonary arteriovenous malformation in children: essential value of contrast echocardiography in diagnosis - Zahari, Norazah; Abd Rahman, Amir Hamzah; Yubbu, Putri (Mashhad University of Medical Sciences, 2017)
Pulmonary arteriovenous malformations (PAVM) are abnormal communications between pulmonary arteries and pulmonary veins, and most commonly congenital in nature. Although rare, it is an important consideration in cyanotic patients of unknown cause. We report 3 cases with diffuse PAVM in children with different clinical manifestations and initial diagnosis was made by transthoracic contrast echocardiogram. Transthoracic contrast echocardiography (TTCE) is valuable as initial diagnostic tools for diffuse PAVM. Pulmonary angiography should be reserved for therapeutic purposes for PAVM rather than diagnostic.